1993
DOI: 10.1128/iai.61.12.5134-5139.1993
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the human complement alternative pathway by Listeria monocytogenes: evidence for direct binding and proteolysis of the C3 component on bacteria

Abstract: The capacity of the intracellular pathogen Listeria monocytogenes to activate the alternative pathway of human complement was examined. Incubation of L. monocytogenes with human serum in optimal conditions (20% Mg2+EGTA [ethylene glycol-bis(beta-aminoethyl ether)-N,N,N',N'-tetraacetic acid]-chelated serum) consumed (31.3 +/- 3.9)% of C3 hemolytic activity and led to similar amounts of C3 deposition among the 27 strains tested, except for a rough mutant and the penicillin-induced L forms of strain EGD, which bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The efficient capture of C3b/iC3b-coated particles in the sinusoidal lumen is likely the result of high avidity multivalent interactions between CRIg molecules concentrated at the tip of macrophage membrane extensions and multimers of C3b and iC3b on the pathogen surface. Moreover, while CR3 only binds iC3b-coated particles, CRIg binds to C3b, the first C3 cleavage product formed on serum-opsonized pathogens (Gordon et al, 1988;Croize et al, 1993). Binding to C3b in addition to iC3b ensures immediate pathogen recognition through CRIg.…”
Section: Kupffer Cells Complement and Pathogen Recognitionmentioning
confidence: 99%
“…The efficient capture of C3b/iC3b-coated particles in the sinusoidal lumen is likely the result of high avidity multivalent interactions between CRIg molecules concentrated at the tip of macrophage membrane extensions and multimers of C3b and iC3b on the pathogen surface. Moreover, while CR3 only binds iC3b-coated particles, CRIg binds to C3b, the first C3 cleavage product formed on serum-opsonized pathogens (Gordon et al, 1988;Croize et al, 1993). Binding to C3b in addition to iC3b ensures immediate pathogen recognition through CRIg.…”
Section: Kupffer Cells Complement and Pathogen Recognitionmentioning
confidence: 99%
“…In previous studies we have shown that, most likely through C3bi and C1q receptors [16][17][18] , Listeria attracts and infects MDSC 10 . These MDSC are present in large numbers in patients and mice with cancer 11,19 .…”
Section: Introductionmentioning
confidence: 99%
“…However, complement plays an important role in the innate immunity against gram‐positive bacteria as an opsonizing system enhancing their phagocytosis by polymorphonuclear (PMN) and macrophages [27]. It has been shown that human C3 binds on L. monocytogenes through activation of the alternative complement pathway, but the activation does not lead to the membrane attack complex mediated bacterial lysis [29]. In the present study, the inhibition of complement in serum by compstatin resulted in lower bactericidal effect against L. monocytogenes .…”
Section: Discussionmentioning
confidence: 99%